Proper management of pulmonary hypertension crisis - Aziz, Indra Jabbar; Martini, Heny (Heart Science Journal, 2025)
A pulmonary hypertensive crisis is characterized by a sudden increase in the pressure in the pulmonary arteries, leading to an excessive workload on the right ventricle of the heart and a decrease in cardiac output. Typically, individuals with pulmonary hypertension (PH) have a greater mortality rate after surgical procedures, which can range from 4% to 24%. Early recognition of pulmonary hypertensive crisis is crucial. There are a limited number of comprehensive guidelines or review articles that focus on the evaluation and treatment of pulmonary hypertension crises. Hypoxia in pulmonary hypertension crisis leads to a vicious cycle of decreased cardiac output, elevated pulmonary vascular resistance, right ventricular enlargement, restricted left ventricular filling, reduced blood pumping, systemic hypotension, and metabolic and respiratory acidosis. It is crucial to monitor clinical parameters, including systemic hypotension, hypoxia, tachycardia, reduced urine output, and complete absence of urine production. The main characteristics of a pulmonary hypertension crisis are increasing pulmonary and right atrial pressures along with a decrease in cardiac output. Echocardiography can be a useful additional tool that shows the deterioration of the right ventricular (RV) function and enlargement. Confirmation of a pulmonary hypertensive crisis is achieved with the use of invasive hemodynamics. Our current review aims to discuss the proper management of Pulmonary Hypertension Crisis.